Haptoglobin 2-2 genotype is associated with increased risk of cardiovascular disease in patients with rheumatoid arthritis: a matched case-control study - Xu, Chuanhui; Khin, Lay Wai; Tam, Hui Zhen; Goh, Liuh Ling; Koh, Ee Tzun; Dalan, Rinkoo; Leong, Khai Pang (Frontiers in Medicine, 2024)
Introduction Traditional risk factors do not fully explain the increased risk of cardiovascular disease (CVD) in patients with rheumatoid arthritis (RA). The Haptoglobin (Hp) 2-2 genotype confers a lower anti-oxidant and higher inflammatory effect on the vasculature compared to the non-Hp 2-2 genotype. This study investigates the association of the Hp genotype with CVD in patients with RA. Methods Data from 69 RA patients with CVD and 207 sex- and ethnicity-matched RA patients without CVD, collected from 1 January 2000 to 31 December 2020, were retrieved from the Tan Tock Seng Hospital RA Registry. CVD was examined against demographics, clinical and laboratory variables in univariate models. Associations between the Hp genotypes and CVD were analyzed using conditional logistic regression. Results We studied 276 patients (65.2% female, 82.6% Chinese, median age 60.9 years). Most participants were in low disease activity or remission (79.3%). The Hp 2-2 genotype was present in 49.6% (137/276). In the group with CVD, the prevalence of the Hp 2-2 genotype was 50.9% (29/57) in the Chinese, 100% (5/5) in the Indians, and 28.6% (2/7) in the Malays. In the non-CVD group, the respective prevalence was 46.8% (80/171), 66.7% (10/15), and 52.4% (11/21). In univariate analysis, the matched odds ratio (OR) of the Hp 2-2 genotype for CVD in RA was 1.34 [95% confidence interval (CI): 1.22–1.47; p < 0.001]. The Hp 2-2 genotype was significantly associated with CVD (adjusted matched OR: 1.13; 95% CI: 1.01–1.27; p = 0.033) in the multivariate logistic regression model after adjusting the confounding factors, including age, smoking, diabetes, hypertension, hyperlipidemia, anti-CCP autoantibodies, and disease activity. Conclusion The Hp 2-2 genotype is associated with an increased risk of CVD in patients with RA in this multi-ethnic cohort.